Mechanochemical Properties of Individual Human Telomeric RNA (TERRA) G‐Quadruplexes. Issue 15 (26th August 2013) - Yangyuoru, Philip M.; Zhang, Amy Y. Q.; Shi, Zhe; Koirala, Deepak; Balasubramanian, Shankar; Mao, Hanbin
<x xml:space="preserve">Abstract</x> Potential functions: By following the unfolding and refolding of individual human RNA telomeric (TERRA) G‐quadruplexes (GQs) in laser tweezers, the mechanical stability and transition kinetics of RNA GQs are obtained. Comparison between TERRA and DNA GQs suggests their different regulatory capacities for processes associated with human telomeres.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>